Effects of Diltiazem Versus Digoxin on Dysrhythmias and Cardiac-Function after Pneumonectomy - Amar, D. (Institutional Knowledge at Singapore Management University, 1997)
This prospective study was designed to determine whether diltiazem is superior to digoxin for the prophylaxis of supraventricular dysrhythmias (SVD) after pneumonectomy or extrapleural pneumonectomy (EPP) and to assess the influence of these drugs on perioperative cardiac function.